3rd International Conference of Indonesia Society for Remote Sensing (ICOIRS 2017). (June 2018) - Unknown
Abstract : On behalf of the local organizing committee, I would like to welcome you all to The 3rd International Conference of Indonesia Society for Remote Sensing (ICOIRS 2017) – PIT MAPIN XXIV will be held at Semarang on 31 October – 1 November 2017. This Program is part of the 60th Anniversary of Diponegoro University in 2017. The Conference is organized by collaboration of Indonesian Society for Remote Sensing (ISRS/MAPIN), PUI – PKMBRP (Center of Excellent for Science and Technology – Center for Coastal Mitigation and Rehabilitation Studies) Diponegoro University, PUI – PPPJ (Center of Excellent for Science and Technology – Center for Utilization of Remote Sensing) Indonesian National Institute of Aeronautics and Space, BIG (Geospatial Information Agency) and Oceanography Department, Faculty of Fisheries and Marine Science, Diponegoro University under the theme "Global Cooperation for Conserving The Earth". This program is supported by International Society for Photogrammetry and Remote Sensing (ISPRS), Faculty of Engineering, such as Geodesy, Urban & Regional Planning, Geology Department and Center for Spatial Data Infrastructure Development (PPIDS) of Diponegoro University. Over 150 papers and 300 participants are expected in this conference. The event will bring together researchers, policy makers, and practitioners from developed and developing countries to share insights into the challenges and opportunities of remote sensing technology and its application in solving the problems of Indonesia and South East Asia countries. It will showcase cutting-edge research from around the South East Asia, focusing on themes of equity and risk, learning, capacity building, methodology, and possibly investment approaches in remote sensing. It will explore practical adaptation policies, approaches and share strategies for decision making to support global cooperation for conserving the earth.